The Influence of the Digital Entrepreneurship Education Ecosystem on Generation Z's Entrepreneurial Readiness Through Digital Entrepreneurship Literacy: An Experiential Learning Perspective - Arisah, Nur; Subur, Hikmayani; Purnamasari, Wulan; Hasan, Muhammad (International Journal of Economics, Business and Innovation Research, 2025)
This study aims to analyze the influence of the digital entrepreneurship education ecosystem through digital entrepreneurship literacy on the entrepreneurial readiness of Generation Z. In the digital era, Generation Z has great potential for entrepreneurship, but often the lack of understanding regarding the basics of entrepreneurship and digital technology hinders their readiness to start a business. This study adopted a quantitative approach using a questionnaire as a data collection instrument, which was distributed to 420 Generation Z students in Makassar City who had participated in digital entrepreneurship education. Data analysis used was path analysis using several software for data processing such as Microsoft Excel 2010, SPSS (Statistical Product and Service Solution) version 20.0, and Partial Least Squares (PLS) techniques using SmartPls (version 4.0). The results of the study indicate that digital entrepreneurship learning and digital industry collaboration significantly influence digital entrepreneurship literacy and entrepreneurial readiness. In contrast, digital entrepreneurship training and digital business incubators did not significantly influence these two variables. This study suggests the need to improve the quality of digital entrepreneurship learning and collaboration with industry to strengthen the entrepreneurial readiness of Generation Z. Furthermore, digital business training and incubators should be optimized by aligning the materials with the latest technological needs.